From Metabolic Syndrome to Type 2 Diabetes in Youth - Dario Iafusco; Roberto Franceschi; Alice Maguolo; Salvatore Guercio Nuzio; Antonino Crinò; Maurizio Delvecchio; Lorenzo Iughetti; Claudio Maffeis; Valeria Calcaterra; Melania Manco (MDPI AG, 2023)
In the frame of metabolic syndrome, type 2 diabetes emerges along a continuum of the risk from the clustering of all its components, namely visceral obesity, high blood pressure and lipids, and impaired glucose homeostasis. Insulin resistance is the hallmark common to all the components and, in theory, is a reversible condition. Nevertheless, the load that this condition can exert on the β-cell function at the pubertal transition is such as to determine its rapid and irreversible deterioration leading to plain diabetes. The aim of this review is to highlight, in the context of metabolic syndrome, age-specific risk factors that lead to type 2 diabetes onset in youth; resume age specific screening and diagnostic criteria; and anticipate potential for treatment. Visceral obesity and altered lipid metabolism are robust grounds for the development of the disease. Genetic differences in susceptibility to hampered β-cell function in the setting of obesity and insulin resistance largely explain why some adolescents with obesity do develop diabetes at a young age and some others do not. Lifestyle intervention with a healthy diet and physical activity remains the pillar of the type 2 diabetes treatment in youth. As to the pharmacological management, metformin and insulin have failed to rescue β-cell function and to ensure long-lasting glycemic control in youth. A new era might start with the approval for use in pediatric age of drugs largely prescribed in adults, such as dipeptidyl peptidase-4 and sodium-dependent glucose transport inhibitors, and of new weight-lowering drugs in the pipeline such as single and multiple agonists of the glucagon-like peptide 1 receptor. The latter drugs can have tremendous impact on the natural history of the disease. By treating diabetes, they will reduce the burden of all the metabolic abnormalities belonging to the syndrome while causing a tremendous weight loss hitherto never seen before.